(3cfR GdYdhe hOQ GdefXhe aj MbGFb Yde GdTQjYI hObGFb Yde GdWHjYIs - (3LeGd GdOjf eMeO Hf Ydj (B((3Gh YHO Gddg(B) (3Hf JheQJ GdeUehOj GdHQHQj GddbH HGdegOj, GdegOj,J (B524 (3g` s
(3ChdgG (B:s
(3CeG HYO aEf dcd YGde efgGLkG jfgL ajg ef GdYdhe Edi GdCge aGdCge heYQGLkG jYQL Hg ajgG Edi SeG eYGdi Gdgee s
(3BNQgG (B:s
(3agh Yde ZGeV WHjYI QhMi EdgGei aGYed Hg agh UMjM eLQH Je GdcJGH GdeHGQc HMeO Gddg hYhfg hMSf Jhajbg s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3GdCMeOjI (B_ (3JhfS (B(4701) s
Keywords: (3GdJhMjO hGdedd hGdfMds